(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The way of life of each statecountry is reflected in its native society and to understand this society, the study of native literature gets mandatory. Mother India has a rich and fluctuated culture heritage. It has gotten a home to a few positions, ideology, networks and ethnic people each having its very own unconventional literary traditions. Human identity in a world of tangled relationship is causing perplexity of identity which uncovers the equivocal idea of human personality. Fundamentally, deficient and flawed, the human creatures scan and take a stab at achieving the unattainable goals of completeness and perfection. The best answer for the issue of identity emergency at that point is compromise with one’s own self and environment. A guard of society is looking towards change and an indispensable connection among man and society. Literature records the longing and regrets of all segments of society. Accordingly, with the assistance of this paper I might want to present AO Temsula’s desire to investigate the unexplored one who is neither commending nor nullifying Indian nationalism in the stories.